FROM FARM TO TABLE. MANAGEMENT AND MARKETING FOR SMALL FARMERS - Iuliana CETINA; Violeta RADULESCU; Dumitru GOLDBACH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Management and marketing strategies for agrofood production and European distribution policies for agriculture are centered on production. EU and Romania pay huge subsidies to farmers. However, all this policies concern the first link in the chain of food production and distribution. The Romanian small farmer is stimulated to produce raw materials then to sell them at a very low price in the absence of adequate storage spaces. This can increase the value added by selling finished products. Even if it produces finished products, the small producer does not reach the consumer but an intermediary, a link in the distribution chain, as in vegetables and fruits production. In this article we propose a model to shorten and streamline the distribution chain from producer to consumer. The first strategy is to create an associative form that establishes policies regarding the production, what to produce and in what quantities, depending on the demand on the market, whether to sell unprocessed products or to make some small canned goods. The second is the realization of a price strategy, which will be realized after a research among the consumers. The third policy is to determine how the products are distributed and exactly where. The last strategy, but not least, is to create a local brand and promote it among consumers. There will also be small processing units for finished products. All decisions will be made after conducting a research among consumers, the necessary research to find out the consumers preferences regarding the price, brand and other aspects that will be the basis for realizing the policies of the associative form. One of the biggest challenges will be to convince the small Romanian producers to associate, being very well known that they do not want to associate unless they have a real motivation, which is most often financial or the safety of selling of their products. We choose an interdisciplinary approach, using both management and marketing tools due to the complexity of the studied problem, both upstream, that is production, and downstream, distribution.